2020
DOI: 10.1016/j.scriptamat.2020.02.027
|View full text |Cite
|
Sign up to set email alerts
|

The mechanistic implications of the high temperature, long time thermal stability of nanoscale Mn-Ni-Si precipitates in irradiated reactor pressure vessel steels

Abstract: Post irradiation annealing (PIA) clarified the induced versus enhanced controversy regarding nanoscale Mn-Ni-Si precipitate (MNSP) formation in pressure vessel steels. Radiation induced MNSPs would dissolve under high temperature PIA, while radiation enhanced precipitates would be stable above a critical radius (rc). A Cu-free, high Ni steel was irradiated with 2.8MeV Fe 2+ ions at two temperatures to generate MNSPs with average radii (̅) above and below an estimated rc for PIA at 425°C up to 52 weeks. Atom pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 36 publications
3
16
0
Order By: Relevance
“…To summarise, Mn-Ni-Si-rich precipitates have been observed to form in the absence of other precipitates in thermally-aged materials for the first time. Our findings indicate that their formation, particularly at heterogeneous nucleation sites, is thermodynamically favourable from 330 °C up to 405 °C, supporting the findings in Reference [18]. However, the key nucleation mechanism for Mn-Ni-Si-rich precipitate formation is at dislocations and interfaces in the thermally-aged materials, as opposed to in the grain interiors in the neutronirradiated materials; this indicates that the features form at defect sites, and that precipitate formation and growth in neutron-irradiated materials is enhanced due to the production of vacancies during irradiation.…”
Section: Elementsupporting
confidence: 91%
See 1 more Smart Citation
“…To summarise, Mn-Ni-Si-rich precipitates have been observed to form in the absence of other precipitates in thermally-aged materials for the first time. Our findings indicate that their formation, particularly at heterogeneous nucleation sites, is thermodynamically favourable from 330 °C up to 405 °C, supporting the findings in Reference [18]. However, the key nucleation mechanism for Mn-Ni-Si-rich precipitate formation is at dislocations and interfaces in the thermally-aged materials, as opposed to in the grain interiors in the neutronirradiated materials; this indicates that the features form at defect sites, and that precipitate formation and growth in neutron-irradiated materials is enhanced due to the production of vacancies during irradiation.…”
Section: Elementsupporting
confidence: 91%
“…Hence, there is still discussion as to whether these features are thermodynamically stable phases [12,15], which form at an enhanced rate due to the damage induced during irradiation, or are irradiation-induced [16,17]. Recent annealing experiments indicate that the features which form during irradiation are stable at temperatures of 425 °C [18].…”
Section: Main Textmentioning
confidence: 99%
“…Miller et al observed the dissolution of MnNi-rich clusters and uniform distribution of Ni and Mn after post-irradiation annealing (24 h, 723 K) in neutron-irradiated low copper VVER-1000 RPV steel [13]. Conversely, some studies also reported that MNPs with r<r c (r c is the critical radius) dissolved, while those with r>r c occur to coarsen after post-irradiation annealing (673 K) in irradiated RPV steels [49,50]. Notably, those samples in [49] and [50] have a higher Ni content with ∼1.6 wt.%.…”
Section: The Formation Mechanism Of B2 Mnni Phasesmentioning
confidence: 99%
“…Most Fe-Cr-based commercial alloys, such as T91, have been known to form MNSP under both neutron [3,4,8,28,[33][34][35][36][37][38] and proton irradiation [3,26,27,29,39,40]. Furthermore, [33] have shown that parallels can be drawn between the understanding of precipitation in reactor pressure vessel (RPV) steels (low alloy ferriticbainitic steels [41][42][43][44][45][46][47][48][49]) and Fe-Cr based alloys (T91, HT9 etc) [1,2,27,50]. The major differences between RPV steels and Fe-Cr steels are that the latter's solute contents (Ni, Si, Mn, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…are typically much less and latter's neutron irradiation environmental conditions experience higher doses (>10 dpa) and temperatures (300 -550 o C). Thus, embrittlement at high doses suggests that solute segregation to and heterogeneous nucleation on dislocations could be the cause of clustering rather than solute supersaturation (since the solute contents in Fe-Cr are low) [46,49,[51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%